1994
DOI: 10.1021/jm00046a027
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamides Bearing Pendant .alpha.-Sialoside Groups Strongly Inhibit Agglutination of Erythrocytes by Influenza A Virus: Multivalency and Steric Stabilization of Particulate Biological Systems

Abstract: An alpha-sialoside linked to acrylamide by a short connector (5-acetamido-2-O-(N-acryloyl-8-amino-5-oxaoctyl)-2,6-anhydro-3,5-d ideoxy-D-galacto-alpha-nonulopyranosonoic acid, 1) was prepared. Compound 1 formed high molecular weight copolymers with acrylamide, derivatives of acrylamide, and/or vinylpyrrolidone upon photochemically-initiated free radical polymerization. Those copolymers for which the substituents on the acrylamido nitrogen were small inhibited the agglutination of chicken erythrocytes induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
184
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(195 citation statements)
references
References 22 publications
4
184
0
6
Order By: Relevance
“…We attribute the enhanced toxicity attenuation properties of the sialic acid containing polymers to the increased sialic acid valency in these materials. There are many examples of the role of valency in adhesion of ligands to multivalent materials [48][49][50][51][52][53]. More specific to Aβ, others have shown for biological membranes that Aβ binding affinity to sialic acid containing gangliosides increased in clustered or multivalent regions of the membrane compared to membrane regions where sialic acids or gangliosides were unclustered [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…We attribute the enhanced toxicity attenuation properties of the sialic acid containing polymers to the increased sialic acid valency in these materials. There are many examples of the role of valency in adhesion of ligands to multivalent materials [48][49][50][51][52][53]. More specific to Aβ, others have shown for biological membranes that Aβ binding affinity to sialic acid containing gangliosides increased in clustered or multivalent regions of the membrane compared to membrane regions where sialic acids or gangliosides were unclustered [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…77 Many multivalent inhibitors, including neoglycopolymers, have been synthesized for biological applications. 78,79 Dendrimers are attractive scaffolds for constructing multivalent ligands because of their globular shape and the high local density of ligand presentation on the surface. 80 -82 By applying our chain-walking methodology, we found that the simple copolymerization of ethylene with a mannose-containing comonomer (13) at a low value of P E and a low comonomer concentration resulted in a mannose-coated dendritic copolymer.…”
Section: Chain Walking: a New Strategy For Controlling Polymer Topologymentioning
confidence: 99%
“…In particular, small-molecule inhibitors covalently conjugated to a biocompatible polymer have been reported to inhibit human influenza strains (17) and prevent influenza binding to red blood cells (18,19). We have previously shown that the antiviral efficacy of ZA is dramatically enhanced when multiple copies thereof are attached via a flexible linker to the benign and biodegradable polymer poly-L-glutamine (PGN) (20): the resultant PGN-attached drug (PGN-ZA) is 1,000-to 10,000-fold more potent than monomeric ZA in plaque reduction assays and, importantly, is effective even against ZA-and oseltamivir-resistant influenza viruses.…”
mentioning
confidence: 99%